2009
DOI: 10.1111/j.1863-2378.2008.01183.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Highly Specific and Cross‐Reactive Antigens of Leishmania Species by Antibodies from Leishmania (Leishmania) chagasi Naturally Infected Dogs

Abstract: The Leishmania species present a genetic homology that ranges from 69 to 90%. Because of this homology, heterologous antigens have been used in the immunodiagnosis and vaccine development against Leishmania infections. In the current work, we describe the identification of species-specific and cross-reactive antigens among several New World Leishmania species, using symptomatic and asymptomatic naturally Leishmania chagasi-infected dog sera. Soluble antigens from five strains of New World Leishmania were separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Leishmania chagasi ) from Brazil have been shown to respond to antigen from L. major -like antigen by ELISA [24] and also to L. braziliensis antigen [25]. Furthermore, sera from Brazilian L. infantum ( chagasi )-infected dogs was reactive by western immunoblotting with several antigens from whole promastigote antigens of Leishmania guyanensis , Leishmania amazonensis and L. braziliensis [26]. Therefore, cross-reactivity amongst the Old World species of L. major , L. tropica and L. infantum as found in dogs in the current study is not surprising, and it is important to note that ELISA has not been found distinctive for the infecting Leishmania species with regard to the OD level of reactivity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Leishmania chagasi ) from Brazil have been shown to respond to antigen from L. major -like antigen by ELISA [24] and also to L. braziliensis antigen [25]. Furthermore, sera from Brazilian L. infantum ( chagasi )-infected dogs was reactive by western immunoblotting with several antigens from whole promastigote antigens of Leishmania guyanensis , Leishmania amazonensis and L. braziliensis [26]. Therefore, cross-reactivity amongst the Old World species of L. major , L. tropica and L. infantum as found in dogs in the current study is not surprising, and it is important to note that ELISA has not been found distinctive for the infecting Leishmania species with regard to the OD level of reactivity in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite testing positive serologically, three dogs from the asymptomatic group, including a three-to-four-month-old puppy, tested negatively for all of the administered tests. Possible explanations include false seropositivity 40 , cross-reactivity with other diseases 41 or the presence of a pre-patent infection 42,43 . In the case of the puppy, the positive serology might also be attributable to the presence of maternal antibodies 44 .…”
Section: Discussionmentioning
confidence: 99%
“…The presence of antibodies against T. gondii, N. (VALE et al, 2009), and seropositive results only for the genus (Leishmania spp.) were considered in this study.…”
Section: Resultsmentioning
confidence: 99%